Kolaborasi Pengelolaan Sawah untuk Ketahanan Pangan Rumah Tangga: Kasus Santri Tani Kabupaten Sukabumi - Ekarini, Farina; Mardiana, Rina (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2022)
The collaborative rice field management that has been carried out in Ciracap Village, Ciracap District, Sukabumi Regency, aims to achieve the level of food security of farmer households. The stakeholders have roles as capital providers, facilitators, and off-takers. This study aims to analyze the extent to which the effectiveness of collaboration can provide positive changes to the level of food security of farmer households in Ciracap Village. This research started from February to August 2021, using mixed methods. The data collected was obtained based on a survey method with a questionnaire instrument for quantitative methods, as well as observations and in-depth interviews for qualitative methods. Quantitative data were processed using a multivariate test with MANOVA analysis, while qualitative data is processed by data reduction, data presentation, and data verification. The results showed that the collaborative process of rice field management was based on a high level of trust between the closest stakeholders. However, based on the administrative data that is not on field conditions, the effectiveness of the collaboration process on the level of household food security is less effective. The effectiveness of collaboration tends to be weak because the program implementation has not yet fully guaranteed the fulfillment of food for farmer households. This is indicated by the socio-economic conditions of farmers that have not changed positively because the quality and quantity of rice production are not in line with the target.